Open AccessOriginal Article Anesthetic Efficacy of Supplemental Buccal Infiltration as Compared to Intraligamentary Injection in Treating Mandibular Second Molars with Irreversible Pulpitis - Naqvi, Syed Shan E Haider; Rana, Nadeem Ahmad; Ehsan, Hafiz Rabbi ul; Maryum, Shumaila; Khurshid, Talha; Azad, Naseem (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the anesthetic efficacy of supplemental buccal infiltration (BI) and intraligamentary (IL) injections in treating mandibular second molars with irreversible pulpitis in the Pakistani population.Study Design: Quasi experimental study.Place and Duration: Department of Operative Dentistry and Endodontics, Armed Forces Institute of Dentistry, Rawalpindi, Pakistan, from Apr 2024 to Oct 2024.Methodology: This study included 100 participants (median age: 30 years) divided into two groups: IL group and BI group. Patients received standardized local anesthesia protocols, and pain levels were recorded using the Visual Analog Scale (VAS). Pain levels were classified as mild, moderate, or severe, and the success rate of anesthesia was evaluated.Results: The IL group showed significantly lower pain levels (median VAS: 38.00(31.00–41.00)) compared to the BI group (median VAS: 65.50(40.00–87.00)). Severe pain was reported by 21(42.0%) participants in the BI group versus none in the IL group (p